Firefighters’ exposure biomonitoring: Impact of firefighting activitieson levels of urinary monohydroxyl metabolites - Oliveira, Marta (2016)
tThe concentrations of six urinary monohydroxyl metabolites (OH-PAHs) of polycyclic aro-matic hydrocarbons, namely 1-hydroxynaphthalene, 1-hydroxyacenaphthene, 2-hydroxyfluorene,1-hydroxyphenanthrene, 1-hydroxypyrene (1OHPy), and 3-hydroxybenzo[a]pyrene, were assessed inthe post-shift urine of wildland firefighters involved in fire combat activities at six Portuguese firecorporations, and compared with those of non-exposed subjects. Overall, median levels of urinaryindividual and total OH-PAHs ( OH-PAHs) suggest an increased exposure to polycyclic aromatic hydro-carbons during firefighting activities with OH-PAH levels in exposed firefighters 1.7–35 times higherthan in non-exposed ones. Urinary 1-hydroxynaphthalene and/or 1-hydroxyacenapthene were the pre-dominant compounds, representing 63–98% of OH-PAHs, followed by 2-hydroxyfluorene (1–17%),1-hydroxyphenanthrene (1–13%), and 1OHPy (0.3–10%). A similar profile was observed when gen-der discrimination was considered. Participation in fire combat activities promoted an increase of thedistribution percentage of 1-hydroxynaphthalene and 1-hydroxyacenaphthene, while contributions of1-hydroxyphenanthrene and 1OHPy decreased. The detected urinary 1OHPy concentrations (1.73 × 10−2to 0.152 mol/mol creatinine in exposed subjects versus 1.21 × 10−2to 5.44 × 10−2 mol/mol creatininein non-exposed individuals) were lower than the benchmark level (0.5 mol/mol creatinine) proposedby the American Conference of Governmental Industrial Hygienists. This compound, considered thebiomarker of exposure to PAHs, was the less abundant one from the six analyzed biomarkers. Thusthe inclusion of other metabolites, in addition to 1OHPy, in future studies is suggested to better estimatefirefighters’ occupational exposure to PAHs. Moreover, strong to moderate Spearman correlations wereobserved between individual compounds and OH-PAHs corroborating the prevalence of an emissionsource.